2013
DOI: 10.1016/j.energy.2013.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Bio-synthetic natural gas as fuel in steel industry reheating furnaces – A case study of economic performance and effects on global CO2 emissions

Abstract: Climate change is of great concern for society today. Manufacturing industries and construction account for approximately 20% of global CO 2 emissions and, consequently, it is important that this sector investigate options to reduce its CO 2 emissions. One option could be to substitute fossil fuels with renewable alternatives. This paper describes a case study in which four future energy market scenarios predicting 2030 were used to analyse whether it would be profitable for a steel plant to produce bio-synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…In some cases, the term synthetic natural gas refers to bio-SNG, since biomass has been used to produce the synthetic natural gas [30,31]. In other cases, the word natural is taken out from the term [32], which can be misleading because the composition of synthetic natural gas and synthetic gas is not the same.…”
Section: Synthetic Fuel As a Termmentioning
confidence: 98%
“…In some cases, the term synthetic natural gas refers to bio-SNG, since biomass has been used to produce the synthetic natural gas [30,31]. In other cases, the word natural is taken out from the term [32], which can be misleading because the composition of synthetic natural gas and synthetic gas is not the same.…”
Section: Synthetic Fuel As a Termmentioning
confidence: 98%
“…Process integration studies of various thermochemical biorefinery concepts at different industrial sites have been reported in the literature, such as at a biomass-fired combined heat and power plant (Heyne et al, 2012); pulp and paper mills (Andersson and Lundgren, 2014;Consonni et al, 2009); a mechanical pulp and paper mill co-located with a sawmill plant (Isaksson et al, 2012); a steel plant (Johansson, 2013;Lundgren et al, 2013); a chemical cluster (Holmgren et al, 2014); and oil refineries (Brau et al, 2013;Johansson et al, 2012;Sadhukhan and Ng, 2011). Oxo synthesis is another possible interesting application of biomass-derived syngas (Boerrigter and Rauch, 2006;Spath and Dayton, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Nzihou et al [13] presented a review of synthetic fuel production from biomass in combination with concentrated solar energy. Johansson [14] implemented a case study regarding synthetic natural gas production from biomass for steel industry. An experimental study on co-electrolysis performance and durability was performed in Ref.…”
Section: Introductionmentioning
confidence: 99%